2019
DOI: 10.1002/cssc.201901327
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous Cobalt Iron Borate Grown on Carbon Paper as a Precatalyst for Water Oxidation

Abstract: The key to improving water oxidation is to develop efficient and earth‐abundant catalysts for the oxygen evolution reaction (OER). Herein, a new amorphous cobalt iron borate supported on 3D carbon paper integrated electrode is reported as a precatalyst for the OER, which was synthesized by using a one‐pot hydrothermal method. An optimum OER activity was obtained at 25 % Fe doping by screening the compositions of the Co and Fe. The best synthesized catalyst needs an overpotential of 227 mV to deliver a current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 56 publications
(107 reference statements)
1
12
0
Order By: Relevance
“…S4†) indicates that the valence of Fe is 3+. 38–40 X-ray absorption near-edge structure (XANES) and extended X-ray absorption fine structure (EXAFS) spectra were used to probe the chemical valence and surrounding coordination environment of the prepared catalysts. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S4†) indicates that the valence of Fe is 3+. 38–40 X-ray absorption near-edge structure (XANES) and extended X-ray absorption fine structure (EXAFS) spectra were used to probe the chemical valence and surrounding coordination environment of the prepared catalysts. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The boronized NiFe alloy exhibited higher intrinsic catalytic activity, compared to the state-of-the-art materials in 1 M KOH, while presenting excellent catalytic stability for over 3000 h (see Figures 12b and 12c). Cao et al 180 also found that amorphous CoFe bimetallic borates experienced a direct transformation from CoFe borate to CoFeOOH during the OER measurement and the CoFeOOH served as effective catalytic centers within the OER process. Furthermore, the generation of mixed-metal oxide/(oxy)hydroxide through in situ electrochemically transformation has also been reported for transition-metal sulfides and selenides.…”
Section: Fe-containing Catalysts With Other Metal Elementsmentioning
confidence: 95%
“…The boronized NiFe alloy exhibited higher intrinsic catalytic activity, compared to the state-of-the-art materials in 1 M KOH, while presenting excellent catalytic stability for over 3000 h (see Figures b and c). Cao et al also found that amorphous CoFe bimetallic borates experienced a direct transformation from CoFe borate to CoFeOOH during the OER measurement and the CoFeOOH served as effective catalytic centers within the OER process. Furthermore, the generation of mixed-metal oxide/(oxy)­hydroxide through in situ electrochemically transformation has also been reported for transition-metal sulfides and selenides. ,, It is widely accepted that metal oxides are thermodynamically more stable than metal sulfides under highly oxidizing conditions and metal phosphides and metal nitrides are less stable than metal sulfides. , Therefore, the mixed-metal compounds have a high possibility of being transformed to oxide/(oxy)­hydroxide during OER measurement (Figure d).…”
Section: The Critical Role Of Fe In Transition-metal-based Catalystsmentioning
confidence: 96%
“…Hydrogen production via water electrolysis is regarded as a promising technique for developing clean energy to replace fossil fuels. Considering the sluggish reaction kinetics of the oxygen evolution reaction (OER), designing earth-abundant OER catalysts with high catalytic activity and satisfied operational stability is of great importance for further improving the overall efficiency of water splitting. To date, great efforts have been devoted to the exploration of transition metal-based OER catalysts in various structures, including spinel structures, layered structures, perovskite structures, amorphous structures, , and so forth. Aiming on improving the OER activity, enriching the active sites (or facilitating the in situ formation of active species via preoxidation reactions) and enhancing the intrinsic activity of the single site are two basic principles .…”
Section: Introductionmentioning
confidence: 99%